2021
DOI: 10.3390/ijerph19010129
|View full text |Cite
|
Sign up to set email alerts
|

Gambling in Spanish Adolescents: Prevalence and Association with Mental Health Indicators

Abstract: Concern about the development of behavioral addictions in adolescence, including gambling, has increased in recent years. Evidence shows that problem gambling can lead to personal, social, or health problems. However, even though gambling is an illegal activity, studies on this problem are quite limited in Spain. The main objective of this study was to analyze the prevalence of gambling in adolescents in Spain. Moreover, gambling behaviors were examined according to gender and age, and their possible relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…Yokomitsu et al found the rate of probable problem gambling among students to be 5.1%, close to our study (Yokomitsu et al, 2019). In a study conducted with Spanish adolescents, it was found that 20.6% of the participating adolescents had engaged in gambling in the last 12 months (Pérez-Albéniz et al, 2022). The discrepancy between the results of our study and those of studies conducted in our country may be attributed to the different characteristics of the sample groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Yokomitsu et al found the rate of probable problem gambling among students to be 5.1%, close to our study (Yokomitsu et al, 2019). In a study conducted with Spanish adolescents, it was found that 20.6% of the participating adolescents had engaged in gambling in the last 12 months (Pérez-Albéniz et al, 2022). The discrepancy between the results of our study and those of studies conducted in our country may be attributed to the different characteristics of the sample groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Gambling activities, such as sport bets, scratch cards, or cards for money, are widely spread among adolescents with 60% or more of them that wagered at least once a year ( Calado et al, 2017 ; Pérez-Albéniz et al, 2022 ). Several studies have shown that gambling can lead to harmful consequences even during adolescence ( De Luigi et al, 2018 ; Livazović and Bojčić, 2019 ; Pisarska and Ostaszewski, 2020 ), such as social impairment, school difficulties, and loss of interest in other activities, as described by Gambling Disorder (GD) criteria proposed by the American Psychiatric Association ( APA, 2013 ).…”
Section: Introductionmentioning
confidence: 99%